Nutritional Status of Young School Children in a Rural Environment in Srem District - Nenad Djoric; Veljko Vukicevic (Journal of Anthropology of Sport and Physical Education, 2020)
This research was primarily focused on examining the nutritional status of boys and girls of the young school age. The research was conducted in the rural environment in Srem district and it was based on the Body Mass Index (BMI). This was a transversal research, and the sample included 71 students (34 boys and 37 girls) from the first to the fourth grade of the two primary schools in villages Budjanovci and Nikinci. Measurements included height and weight, and based on them, Body Mass Index (BMI) was calculated. The results of the study showed that the number of underweight children was 1 (1.4%), with normal weight 52 (73.2%), preobese 11 (15.5%) and there were 7 obese students (9.9%). There are no statistically significant differences in the frequency of obesity in all four grades. Considering that obesity at a young school age has a significant effect on obesity and the development of many illnesses in an adult life, it is important to understand this problem in order to do prevention more effectively.